2015
DOI: 10.1175/jcli-d-14-00504.1
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Early Summer Precipitation in the Korean Peninsula and Nearby Regions Based on RCP Simulations

Abstract: In this study, the projected regional precipitation changes over northeast Asia (NEA) during early summer [May–July (MJJ)] for the late twenty-first century (2071–2100) were investigated using a high-resolution regional climate model (WRF3.4) based on the representative concentration pathways (RCPs) induced by the global circulation model (HadGEM2-AO). The increased horizontal resolution of the regional model with a 12.5-km horizontal resolution enabled it to reproduce the terrain-following features reasonably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 68 publications
(56 reference statements)
3
29
0
2
Order By: Relevance
“…The 40‐day accumulated precipitation in the RCP runs is simulated to increase in most domains compared with the HS run; however, the 40‐day accumulated precipitation hours are projected to decrease in all domains (not shown). This result is the same as found in previous studies (e.g., Chen and Sun, ; Oh et al , ; Hong and Ahn, ) that showed increases in precipitation intensity under future climate according to increases in precipitation and decreases in precipitation frequency. Thus, the DS_CYP increases in most domains because of the decrease in precipitation hours in RCP runs compared with the HS run.…”
Section: Agro‐climate Changes Under Rcp Runssupporting
confidence: 92%
“…The 40‐day accumulated precipitation in the RCP runs is simulated to increase in most domains compared with the HS run; however, the 40‐day accumulated precipitation hours are projected to decrease in all domains (not shown). This result is the same as found in previous studies (e.g., Chen and Sun, ; Oh et al , ; Hong and Ahn, ) that showed increases in precipitation intensity under future climate according to increases in precipitation and decreases in precipitation frequency. Thus, the DS_CYP increases in most domains because of the decrease in precipitation hours in RCP runs compared with the HS run.…”
Section: Agro‐climate Changes Under Rcp Runssupporting
confidence: 92%
“…Several previous studies (e.g. Choi et al , ; Ahn et al , ; Baek et al , ; Hong and Ahn, ) showed that HadGEM2‐AO has good performance in simulating the global warming trend and general patterns of current climate over East Asia region. Therefore, our evaluation is only focused on regional climate simulation with 12.5‐km grid spacing derived from RCMs over the analysis domain (117°∼138°E, 29°∼46°N).…”
Section: Methodsmentioning
confidence: 99%
“…Although CMIP5 data are very useful in long‐term climate projection, they are insufficient for investigating a shift in local phenomena such as fine‐scale daily temperature and phenology due to their coarse‐resolution grid system. A dynamical downscaling technique using regional climate model (RCM) has been developed and used as a method of overcoming the limitations arising from the low spatial resolvability of the global model (Im et al , ; Ahn et al , ; Kang et al , ; Oh et al , ; Hong and Ahn, ; Hur and Ahn, ). Thus, dynamical downscaling has been performed with the lateral forcing from CMIP5 data, thereby enabling detailed future climate analyses (Giorgi et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…그러나 이러한 전구 모형의 결과는 낮은 해상도로 인하여 지역규모의 기후 정보 를 산출하기에는 한계가 있다. 반면, 지역기후 모형은 고분해능의 지형 효과 등을 반영함으로써 국지규모의 기후변화 연구에서 매우 유용한 도구로 이용되고 있 다(e.g., Giorgi and Mearns, 1999;Boo et al, 2004;Im et al, 2008;Ahn et al, 2010a, b;Hong and Ahn, 2015;Im et al, 2016). 최근 우리나라는 다섯 개의 지 역기후모델, 즉, RegCM version 4 (RegCM4; Giorgi et al, 2012), Regional Spectral Model (RSM; Hong et al, 2013), Weather Research and Forecasting model (WRF; Skamarock et al, 2005), Seoul National University Meso-scale Model version 5 (SNU-MM5; Lee et al, 2004;Cha et al, 2008), Hadley Centre Global Environmental Model version 3 regional climate model (HadGEM3-RA; Davies et al, 2005)을 이용하 여 국제 공동연구인 Coordinated Regional Climate Downscaling Experiment (CORDEX) 동아시아 1단계 프로젝트에 참여하였으며 Oh et al, 2014;Park et al, 2015), 이에 더하여 12.5 km의 고해 상도를 가지는 한반도 국가표준 기후변화 시나리오도 산출하였다.…”
Section: 서 론unclassified